Tumor Induced Osteomalacia in Patients With Metastatic Prostate Cancer: Case Report and Literature Review - Khadilkar, Arjun (J Endocr Soc, 2021)
Background:Tumor induced osteomalacia (TIO), driven by elevated levels of fibroblast growth factor (FGF23), has been associated with progressive aggressive prostate cancer. FGF23, expressed by osteocytes, plays an important role in tumorigenesis through cell proliferation, chemotaxis, and angiogenesis. FGF23 regulates phosphate homeostasis through feedback loops between the kidney and bone. We present a case report of a patient with TIO and advanced prostate cancer (PC) and review previously published data. Clinical Case: A 63-year old male with castrate-resistant PC with bone metastases presented with symptoms of profound fatigue, memory loss, and brain fog. Laboratory studies demonstrated severe hypophosphatemia (phosphorus 0.8 mg/dL, normal 2.5–4.5 mg/dL), mild hypocalcemia, secondary hyperparathyroidism, normal 25 hydroxy-vitamin D and 1,25-dihydroxy vitamin D. After treatment with IV and oral replacement, phosphorus improved to 2.2 mg/dL. Urinary phosphorous was elevated at 2105 mg/24 hours (normal 400–1300 mg/24 hours) and FGF23 545 RU/mL (normal < 180 RU/mL). His PC treatment regimen extended over 10 years with multiple systemic, radiation, and targeted ablation therapies. He was also on denosumab every 3 months for metastatic bone disease, but it was discontinued due to hypophosphatemia. He is now treated with calcium carbonate-vitamin D 1000 mg-250 IU twice daily, calcitriol 1.5 mcg/daily, Phospha Neutral 250mg 2 tablets four times daily, and abiraterone acetate. His hypophosphatemia, hypocalcemia and secondary hyperparathyroidism has resolved with this regimen. To our knowledge there are 17 cases of TIO in metastatic PC are reported to date. Majority of the patients have similar clinical presentation. Treatment of metastatic PC, as well as calcitriol, phosphorus replacement, octreotide, and cinacalcet were described. Conclusions: FGF23 plays an important role in metastatic prostate cancer progression. TIO is a rare entity in patients with metastatic PC, however mild cases are underdiagnosed due to its nonspecific symptoms and lack of routine screening. The FGF pathway represents a new target for prostate cancer treatment and clinical trials targeting FGF23 pathway in PC are needed for further drug development. Also, the efficacy of burosumab, a novel monoclonal antibody directed against human FGF23 in treatment of hypophosphatemia in metastatic PC requires further investigation.